2018
DOI: 10.1002/lary.27699
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged antibiotic administration for surgical site infection in pediatric laryngotracheal surgery

Abstract: Objectives/Hypothesis: Incidence of surgical site infection (SSI) after laryngotracheal (LT) surgery is relatively high, especially in children. Study Design: Retrospective and prospective cohort study. Methods: Clinical records of children who underwent open LT surgery at the Istituto Giannina Gaslini Children's Hospital from January 2008 to August 2017 were reviewed for development of SSI. Standard antibiotic prophylaxis was administered until February 2015. In March 2015, an antibiotic treatment tailored on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
(24 reference statements)
2
5
0
Order By: Relevance
“…The authors found a significant decrease in SSI with the tailored antibiotic regimen 10 . Based on the consistency between our results and previous findings, 10,11,13,15 we advocate for bacterial screening of the airway with culture directed treatment before airway reconstruction. We believe assessment of lower airway colonization via flexible bronchoscopy with BAL culture is the most effective diagnostic modality, supporting a multidisciplinary aerodigestive evaluation.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The authors found a significant decrease in SSI with the tailored antibiotic regimen 10 . Based on the consistency between our results and previous findings, 10,11,13,15 we advocate for bacterial screening of the airway with culture directed treatment before airway reconstruction. We believe assessment of lower airway colonization via flexible bronchoscopy with BAL culture is the most effective diagnostic modality, supporting a multidisciplinary aerodigestive evaluation.…”
Section: Discussionsupporting
confidence: 88%
“…11 The authors prophylaxis and a culture-directed antibiotic protocol. 10 In the latter group, upper airway and tracheostomy swabs with either tracheal aspirate or BAL were obtained 10 days preoperatively. An antibiotic course was designed to begin 5 days before the procedure based on these results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations